Basic Study of Judges' Consisderations on Unlawful Acts in The Case of Transfer of Rights to State-Owned Enterprise Land in Corruption Crimes - Eva Meita Theodora Pasaribu; Setiyono, Setiyono; Ariyanti, Ariyanti (MLJ Merdeka Law Journal, 2025)
This research aims to analyze and identify the basis of the judge's considerations regarding unlawful acts in the case of the transfer of state-owned enterprise land rights and the application of criminal liability law in the transfer of state-owned enterprise land rights. The type of research used is normative legal research with a statutory approach and a case approach. The results show that the basis for the judge's consideration of unlawful acts in the case of the transfer of state-owned enterprise land rights in corruption should be assessed as a criminal offense, not just a civil one, given that the actions resulted in significant state losses. The HGB approval, which should include legal requirements affirming the defendant's responsibility in safeguarding state interests, was not adhered to. The consignment of IDR 13 billion submitted by the Defendant to PT KAI is considered invalid because Cassation Decision No. 2966 K/Pdt/2013 states that the Defendant had no legal basis for making the consignment, thus it cannot be used as a defense to eliminate the criminal element. Regarding the application of legal certainty in criminal liability for the unlawful transfer of state-owned enterprise land rights, the defendant's actions meet the criminal elements as stipulated in Article 2 Paragraph (1) and Article 3 of the Anti-Corruption Law. The defendant is guilty of committing corruption collectively, which includes elements of unlawful material actions, malicious intent, and state financial loss.